Development of a novel trap for the collection of black flies of the simulium ochraceum complex - Lazzari, Claudio R.; Rodríguez Pérez, Mario Alberto; Adeleke, Monsuru Adebayo; Burkett Cadena, Nathan D.; Garza Hernandez, Javier Alfonso; Reyes Villanueva, Filiberto; Cupp, Eddie W.; Toé, Laurent D.; Salinas Carmona, Mario César; Rodríguez Ramírez, Américo David; Katholi, Charles R.; Unnasch, Thomas R. (Public Library of Science, 2013)
Background: Human landing collections are currently the standard method for collecting onchocerciasis vectors in Africa and Latin America. As part of the efforts to develop a trap to replace human landing collections for the monitoring and surveillance of onchocerciasis transmission, comprehensive evaluations of several trap types were conducted to assess their ability to collect Simulium ochraceum sensu lato, one of the principal vectors of Onchocerca volvulus in Latin America. Methodology/Principal Findings: Diverse trap designs with numerous modifications and bait variations were evaluated for their abilities to collect S. Ochraceum s.l. females. These traps targeted mostly host seeking flies. A novel trap dubbed the “Esperanza window trap” showed particular promise over other designs. When baited with CO2 and BG-lure (a synthetic blend of human odor components) a pair of Esperanza window traps collected numbers of S. Ochraceum s.l. females similar to those collected by a team of vector collectors. Conclusions/Significance: The Esperanza window trap, when baited with chemical lures and CO2 can be used to collect epidemiologically significant numbers of Simulium ochraceum s.l., potentially serving as a replacement for human landing collections for evaluation of the transmission of O. volvulus.